Processes of oxidation and HCl-leaching of Tellnes ilmenite - Janssen, A.; Putnis, Andrew (2011)
Tellnes ilmenite is an important feedstock for the production of high-grade titanium pigment. The present study investigated the oxidation of ilmenite from Tellnes, Norway, at 700 °C in air and compared the leaching ability of pre-heated and non-heated Tellnes ilmenite in 20% HCl solution at 160 °C. Through the heat treatment, ilmenite (FeTiO3) is oxidized to hematite (Fe2O3) and rutile (TiO2) via a solid-state reaction mechanism. The leaching experiments revealed that after the pre-heating step the iron dissolution in the leaching process is limited due to the lower solubility of ferric iron in the hydrochloric acid. Furthermore, in both experiments the impurity phases such feldspar and orthopyroxene are less soluble in the hydrochloric acid and pollute the replacement product rutile because Si released from the impurity phases is incorporated in the rutile. The leaching reaction mechanism is interpreted as a pseudomorphic, interface-coupled dissolution-reprecipitation process, through which the external form of the parent ilmenite as well as its crystallographic orientation is inherited by rutile.